A novel framework to intercept GPS-denied, bomb-carrying, non-military, kamikaze drones: Towards protecting critical infrastructures - Skraparlis, Athanasios N.; Ntalianis, Klimis S.; Tsapatsoulis, Nicolas (My University, 2024)
Protection of urban critical infrastructures (CIs) from GPS-denied, bomb-carrying kamikaze drones (G-B-KDs) is very challenging. Previous approaches based on drone jamming, spoofing, communication interruption and hijacking cannot be applied in the case under examination, since G-B-KDs are uncontrolled. On the other hand, drone capturing schemes and electromagnetic pulse (EMP) weapons seem to be effective. However, again, existing approaches present various limitations, while most of them do not examine the case of G-B-KDs. This paper, focuses on the aforementioned under-researched field, where the G-B-KD is confronted by two defensive drones. The first neutralizes and captures the kamikaze drone, while the second captures the bomb. Both defensive drones are equipped with a net-gun and an innovative algorithm, which, among others, estimates the locations of interception, using a real-world trajectory model. Additionally, one of the defensive drones is also equipped with an EMP weapon to damage the electronics equipment of the kamikaze drone and reduce the capturing time and the overall risk. Extensive simulated experiments and comparisons to state-of-art methods, reveal the advantages and limitations of the proposed approach. More specifically, compared to state-of-art, the proposed approach improves: (a) time to neutralize the target by at least 6.89%, (b) maximum number of missions by at least 1.27% and (c) total cost by at least 5.15%.
Keywords: Critical infrastructure; Kamikaze drone; GPS-Denied; Bomb-carrying; Trajectory estimation